The effect of shipping efficiency on marine petroleum pollution: an empirical analysis of China’s 11 coastal regions - Ji, Xina; Ding, Xingong; Hu, Wanli; Qiu, Yuxi (Frontiers in Marine Science, 2025)
IntroductionMarine petroleum pollution has adversely affected marine ecosystems and human living environments, while improvements in shipping efficiency offer a new avenue for mitigating such pollution.MethodsBased on panel data from 11 coastal regions in China spanning 2010 to 2022, this study examines the impact mechanisms of shipping efficiency on marine petroleum pollution and further analyzes the moderating effects of port specialization and environmental regulation.ResultsThe results indicate that, overall, shipping efficiency in coastal regions has shown a steady upward trend, with an average efficiency index of 1.046 and an annual growth rate of 4.6%. However, some regions, such as Liaoning, Shandong, and Tianjin, have experienced declines in efficiency, highlighting regional disparities in development. Regression analysis reveals a significant negative relationship between shipping efficiency and marine petroleum pollution. The two-way fixed effects model shows that a 0.01 increase in shipping efficiency corresponds to an approximate 0.01% reduction in marine petroleum pollution, suggesting that enhanced shipping efficiency effectively contributes to improving marine environmental quality. Furthermore, the moderating effect analysis demonstrates that both port specialization and environmental regulation exert significant negative moderating effects on the relationship between shipping efficiency and marine petroleum pollution.DiscussionOverall, this study enriches the theoretical understanding of the relationship between the operational efficiency of transport infrastructure and environmental pollution and provides robust empirical support for formulating green and efficient shipping policies and advancing sustainable marine environmental governance in coastal regions.